Importance of inflammatory markers and IL-6 for diagnosis and follow up of patients with type 2 diabetes mellitus - Maja Malenica; Mira Šilar; Tanja Dujić; Tamer Bego; Sabina Semiz; Selma Škrbo; Besim Prnjavorac; Adlija Čaušević (Medicinski glasnik, 2017)
Aim: To analyse the long-term impact of altered metabolism on the level of mediators of inflammatory response in female patients with type 2 diabetes. Methods: This study included 97 female patients with type 2 diabetes and 107 female, nondiabetic control subjects, who were recruited at the Clinical Centre University of Sarajevo and the General Hospital Tešanj. The effects of glycaemic control on markers of inflammatory response represented by C-reactive protein (CRP), fibrinogen, leukocytes, sedimentation rate, and cytokine IL-6 were tested. All subjects were free of evidence of infections, surgery, thyroid disease, polycystic ovarian syndrome, active liver and kidney damage. All biochemical analyses were performed according to standard International Federation of Clinical Chemistry (IFCC) protocols. Results: A significant increase of fibrinogen (p<0.001), CRP (p=0.001), interleukin-6 (p=0.013), leukocytes (p<0.001) and sedimentation rate (p=0.008) in diabetic female population compared to control subjects was found. A significant correlation between CRP and haemoglobin A 1c (p=0.035), interleukin-6 and glucose (p=0.032), IL-6 and body mass index (p=0.007) was found. Conclusion: Our data suggest that inflammation plays an important role in the pathogenesis of diabetes in female diabetic population. A more detailed study on a far larger number of subjects is needed if they were to be used effectively as biomarkers in the primary prevention of type 2 diabetes in this population.
Keywords: inflammation; cytokine; hyperglycaemia